Method for selecting parameters and assessing efficiency of wind-diesel power plants for autonomous electrical supply systems; IOP Conference Series: Materials Science and Engineering; Vol. 289 : Modern Technologies for Non-Destructive Testing - Obukhov S. G. Sergey Gennadievich (2018, 2018)
Title screen